THE GENUS MIMOSA WITH SPECIAL REFERENCE TOM. QUADRIVALVIS L. VAR. LEPTOCARPA (D.C.) EARNEDY, A NEW SPECIES RECORD FOR THE WEED FLORA IN MALAYSIA*) - M. A HAJI MOHAMED; BAKI BAKI,; B. BAKAR; H. NOORMA WATI (SEAMEO BIOTROP, 1996)
An exploratory floristic survey of the genus Mimosa was conducted in 1993 to ascertain species diversity and their spatial patterns of distribution in Peninsular Malaysia. A new species record of uncertain indigene, M.. quadrivalvis was recorded for the first time in restricted localities along the roadsides in Pekan Darat and Bertam, Seberang Perai, Gurun and Bedong in Kedah in addition to widely distributed and seemingly ubiquitous presence of M. invisa Mart. ex. Colla and M. pudica L. The latter two species were mostly found in open, disturbed and derelict habitats, agricultural areas and ex-mining lands. Both species exhibited largely contagious and overdispersed distribution patterns with positive peaks in pattern intensity values although regularity or underdispersed distribution patterns do manifest in certain localities. The giant mimosa, M. pigra inhabited in clustered thickets, large pockets of lands in the urban and sub-urban localities in the states of Penang, Perak, Kelantan, Kuala Lumpur and Negeri Sembilan. In other states, M. pigra was confined to a few localities in smaller patches. Except for M. quadrivalvis, the other species of Mimosa are serious weeds in the agricultural, recreational and residential and derelict areas. A key to the Mimosa species is constructed along with brief descriptions on their morphology and ecology. Key words: Malaysia/Weed ecology/Mimosa invisa/Mimosa pigra/Mimosa pudica/Mimosa quadrivalvis/ Weeddistribution/Weed anatomy and morphology.